Unexpected changes of itinerary – adaptive functioning difficulties in daily transitions for adults with autism spectrum disorder. Issue 3 (2nd July 2016) - Rydzewska, Ewelina
Abstract: Adaptive functioning skills, also known as adaptive behaviours, refer to a multifaceted concept defined as behaviours necessary for age-appropriate, independent functioning in social, communication, daily living or motor areas. In light of the growing population of children with ASD who will eventually become adults, increased understanding of adaptive functioning during the transition to adulthood is of importance, but current research in this area lacks first-hand evidence presenting adaptive skills difficulties among older adolescents and adults with ASD. This article focuses on adaptive functioning skills in daily transitions for adults with Asperger's syndrome (AS) or high-functioning autism (HFA). It draws on evidence from 12 interviews with individuals on the autism spectrum age 16–43, and 2 focus groups with 8 family members of people affected by ASD. Particular emphasis is placed on impact of adaptive functioning difficulties on well-being and quality of life for adults with ASD. Grounded theory approach has been used to analyse the gathered data. Interviewees reflected on daily challenges associated with unexpected changes in routine, sensory difficulties and social interactions. These in turn had an impact on their adaptive functioning skills by introducing complications in the process of making transitions between different contexts and decreasing interviewees' ability to tackle challenges of daily life. Importance placed on societal expectations towards meeting bespoken standards and conforming to norms ruling the structure and interactions of daily life were also widely discussed. Frequently such expectations did not allow for factoring in the developmental nature of ASD and related difficulties, which as a result triggered additional complexity in managing daily transitions for adults on the spectrum. Further research addressing adaptive functioning skills in daily transitions for adults with ASD is needed.